Performance and emission analysis of an internal combustion engine with hydroxy gas assist. (2021) - Mohan, Sreejith; Madhusudhanan, Yedu Krishnan; Salim, Sabari; Nikhil, R.; Vishnu, P.; Sivapirakasam, S.P.; Vishnu, B.R.
Highlights: HHO gas was produced by the electrolytic reaction of water and added alongside fuel. HHO significantly reduced emissions of CO, CO2 emissions and unburnt HC. Vehicle mileage improved by 33% due to the addition of HHO. HHO decreased specific fuel consumption by 26% and improved efficiency by 42%. No major modifications in the engine are required to accommodate HHO system. Abstract: The present study aims at evaluating the performance characteristics of a petrol engine augmented with an HHO generator. The HHO gas was generated by the electrolysis reaction of water. The catalyst used for the reaction was KOH. The HHO gas was allowed to enter the carburettor along with the air–fuel mixture and its effect on the mileage, specific fuel consumption, thermal efficiency and emissions of the engine were investigated. The results revealed significant improvement in the thermal efficiency of the engine supplemented with reduced fuel consumption. Further, a tangible reduction in the emission of CO, CO2, and unburnt HC was noted.